DCD enterprise: multi-level hanger / Cynthia Jane Duanis, Dayang Jerry Panai and Debbie Gloria Peter - Duanis, Cynthia Jane; Panai, Dayang Jerry; Peter, Debbie Gloria (2017)
This business is based on a partnership where it consists of three members who hold important positions in the 'DCD Enterprise' such as General & Administrative Manager, Marketing & Financial Manager and Operational Manager. The business capital amounts to RM38,004.00 where the total contribution of each member is RM 12,688.00